Transcriptome analysis of salt-responsive and wood-associated NACs in Populus simonii × Populus nigra - Yao, Wenjing (BMC Plant Biol, 2020)
BACKGROUND: NAC (NAM, ATAF1–2, and CUC2) family is one of the largest plant-specific transcription factor families known to play significant roles in plant development processes and stress responses. RESULTS: In the study, a total of 112 NACs were identified to be differentially expressed in the comparisons of leaves and stems, leaves and roots, roots and stems of Populus simonii×P. nigra among 289 members by RNA-Seq. And 148, 144 and 134 NACs were detected to be salt-responsive in the roots, stems and leaves under 150 mM NaCl stress, respectively. Among them, a total of 53 salt-responsive NACs were shared across the three tissues. Under salt stress, 41/37 NACs were identified to be up/down-regulated in the leaves of Populus simonii × P.nigra among 170 non-redundant NACs by RT-qPCR, which was similar with RNA-Seq results. The expression pattern analysis of 6 NACs including four randomly up-regulated genes (NAC86, NAC105, NAC139 and NAC163) and two down-regulated genes (NAC15 and NAC149) indicated a few NACs showed specific temporal and spatial expression patterns in the three tissues of Populus simonii×P.nigra. Based on transcriptome screening and phylogenic analysis of differentially expressed NACs in different tissues under salt stress, 18 potential NACs associated with wood formation and 20 involved in stress responses were identified in Populus simonii×P.nigra. CONCLUSIONS: The study further gains an understanding of the connection of tissue specificity and gene function in poplar, and lays the foundation of functional analysis of poplar NACs in stress responses.